Rancang Bangun Aplikasi Sistem Antrian Tamu untuk Mendukung Efektifitas Lahan Parkir Berbasis Online - Hanifah, Izzati Millah; Ruskan, Endang Lestari (Institut Teknologi Garut, 2023)
Guest visits to various government agencies are a common activity. The South Sumatra Provincial Health Service also experienced something similar, where this visit involved various activities such as meetings, hearings, consultations, reporting, and so on. However, with the high frequency of guest visits, various challenges arise, such as employees not being able to determine visit schedules and guests being unable to predict the level of crowds, making it difficult to find a parking space. Several hospitals, such as RSIA Hermina Palembang and Muhammadiyah Hospital Palembang, have implemented a guest visit management system. These systems focus on making patient registration and outpatient administration easier so that there is no more queuing. However, the difference in the problem between the South Sumatra Provincial Health Service and RSIA Hermina and Palembang Muhammadiyah Hospital is the focus on proper scheduling of employees and avoiding accumulation of parking spaces for guests. The right method to overcome this problem is to apply the Rapid Application Development (RAD) methodology, which consists of three stages, namely Requirement Planning, Design, and Implementation. This method involves data collection and analysis which includes literature study, observation, interviews, and filling out questionnaires before designing the system. By using this methodology, we will produce a system that can provide information about the correct guest appointment schedule and avoid accumulation of parking lots by limiting the number of guests arriving at the same time.